Observations of core-mantle boundary stoneley modes - Koelemeijer, P; Deuss, A; Ritsema, J (Wiley, 2013)
Core-mantle boundary (CMB) Stoneley modes represent a unique class of normal modes with extremely strong sensitivity to wave speed and density variations in the D" region. We measure splitting functions of eight CMB Stoneley modes using modal spectra from 93 events with Mw> 7.4 between 1976 and 2011. The obtained splitting function maps correlate well with the predicted splitting calculated for S20RTS+Crust5.1 structure and the distribution of Sdiff and Pdiff travel time anomalies, suggesting that they are robust. We illustrate how our new CMB Stoneley mode splitting functions can be used to estimate density variations in the Earth's lowermost mantle.